Starry messenger a book depicting the life of a famous scientist, mathematician, astronomer, philosopher, physicist, Galileo Galilei - Sis, Peter 1949- (Farrar Straus Giroux, 2000)
Describes the life and work of the courageous man who changed the way people saw the galaxy, by offering objective evidence that the earth was not the fixed center of the universe.